1998
DOI: 10.1590/s0004-282x1998000100003
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X syndrome: clinical, electroencephalographic and neuroimaging characteristics

Abstract: -We studied 11 patients (9 males) with cytogenetic diagnosis of fragile X syndrome (FXS) with the purpose of investigating the neural circuitry involved in this condition. The ages ranged from 8 to 19. All the individuals presented large ears, elongated faces and autistic features. Ten patients had severe mental retardation. Attention disorder was found in 10 individuals. Electroencephalographic recordings were abnormal in 6 of 10 patients examined, showing focal epileptiform discharges predominantly in fronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 19 publications
2
28
0
2
Order By: Relevance
“…Thus, reliable tests for early diagnosis and genetic counseling have to be established for the favor of future generations. Physical and neuropsychiatric examination findings in the patient were in concordance with the literature (Guerreiro et al 1998;Artigas-Pallares and Brun-Gasca 2004). EEG findings were abnormal as well.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, reliable tests for early diagnosis and genetic counseling have to be established for the favor of future generations. Physical and neuropsychiatric examination findings in the patient were in concordance with the literature (Guerreiro et al 1998;Artigas-Pallares and Brun-Gasca 2004). EEG findings were abnormal as well.…”
Section: Discussionsupporting
confidence: 88%
“…The FMR1 gene codes for a cytoplasmic protein called FMRP, which plays role in the cascade of aberrations in neurodevelopment. FMRP is mostly detected in neurons and associated with polyribosomes, including those present in dendrites for synaptic maturation and function (Guerreiro et al 1998). The loss of this specific protein leads to suboptimal structure and function in the central nervous system.…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%
“…Our study concentrates primarily on cortical blood flow in clear cases of autism. Several authors have demonstrated cerebral blood flow abnormalities in autism by SPECT or Wilcox/Tsuang/Ledger/Algeo/Schnurr positron emission tomography technology [Happe and Frith, 1996;Carratala et al, 1998;Guerreiro et al, 1998]. Our study differs significantly by comparing regional blood flow in patients of different ages.…”
Section: Introductionmentioning
confidence: 85%
“…While subjects with WBS tend to be unusually socially outgoing and overly friendly [Jones et al, 2000], subjects with 22q DS are often described as withdrawn [Swillen et al, 1999] or as having flat affect [Bassett et al, 1998], and have an elevated incidence of autisticspectrum diagnoses [Niklasson et al, 2001]. In addition, subjects with both Fragile X and Joubert syndrome also typically possess social and communication problems resembling autistic behavior [Cohen et al, 1991;Holroyd et al, 1991], and these disorders have both have been shown to have decreased cerebellar vermal areas [Holroyd et al, 1991;Guerreiro et al, 1998]. Thus, comparison of neurogenetic disorders with prominent affective components suggests that there may be a possible relationship between posterior vermis size and level of social drive.…”
Section: To the Editormentioning
confidence: 99%